Unusual Iatrogenic Complication of ACL Surgery: On the Cartilage Placement of Fixation Material - Sargın, Serdar (Orthop J Sports Med, 2014)
OBJECTIVES: Anterior cruciate ligament (ACL) ruptures constitute the most common ligament injury of the knee, and ACL reconstruction is a commonly performed procedure in orthopedic sport medicine. We report a case of on-the-cartilage placement of EndoButton for ACL reconstruction and its treatment with arthroscopic removal. The rehabilitation method was successful, resulting in excellent function and range of motion of the knee. The aim of this study was present an unusual case of iatrogenic complication of ACL reconstruction and to highlight to the surgeons about this complication. METHODS: A 22-year-old male patient administered to our outpatient clinic with a history of trauma to his left knee in a soccer game 2 years ago. He underwent arthroscopic transtibial ACL reconstruction using hamstring tendons and EB system in another facility 19 months ago. At the time of initial administration he complained about pain and friction on his left knee, especially when he was running. In his physical examination patellar friction, anterior drawer and lachman tests were pathological which reminded us rerupture of ACL. Knee movements were in normal limits, but he felt pain especially during flexion and extension. RESULTS: We used standard anteromedial and anterolateral portals and an accessory portal for excision of EB. When we explored the knee arthroscopically, we observed the EB misplaced on femoral groove. Firstly the loop of EB was cut then the EB was removed from superolateral portal. Loop remnant was cauterized with RF probe. The knee was irrigated and portals were sutured. The operation was finished without complication. The knee was dressed and the patient was kept in an adjustable knee brace. There was no complaint of crepitation and the range of motion (ROM) of knee was in normal limits. We offered revision operation again but the patient didn’t accept this suggestion. CONCLUSION: EB is a good and a commonly used option in ACL reconstruction surgery. Even the complication rates seem much more acceptable when compared to other fixation methods; misplacement of fixation device can be seen. In such a situation it is believed that, surgeons must not hesitate for arthroscopic removal and revision surgery.